PSIKOLOGI TOKOH MIRA DAN MAUDY DALAM FILM “ME VS MAMI” KARYA ODY C HARAHAP - Triek Wahyuda Saputri; Martono Martono; Agus Wartiningsih (Universitas Tanjungpura, 2019)
AbstractThis study aimeds to describe the good character of Mira and Maudy characters as reflected in the id, ego, and super ego in the film “Me vsMami” by Ody C Harahap and the plan for implementing the results of research on learning in school. This study used a psychoanalysis approach. Source data for the film “Me vsMami” with data in the form of words, phrases, actions, and expressions of the characters. Data collection techniques and tools namely documentary studies and researchers as key instruments. Data analysis techniques analyze and interpretion data based on id, ego, and super ego. This study produces data in the form of Mira’s character reflected in the id, ego, and super ego: stubborn, caring, responsible, emotional, merciful. Maudy’s character is refleted in the id, ego, and super ego: careful, perfectionist, responsible, caring, stubborn, compassionate, emotional in the film “Me vsMami” by Ody C Harahap, the plan to implement the results of research on learning in school.Keywords:Character, Personality, Psychoanalysis